Agricultural growth in Argentina - Mundlak, Yair; Domenech, Roberto (International Food Policy Research Institute, 1995)
The most striking characteristic of Argentina's economic history in the twentieth century is the sharp decline in its growth performance. Between 1900 and 1930 Argentina outperformed countries with similar resource endowments such as Australia, Brazil, Canada, and the United States. It lost its lead in the 1930s, and since then it has fallen further and further behind these countries. Not only was the average growth rate low, but the performance was also subject to wide fluctuations. The deterioration reached its peak in the 1980s, when per capita output declined at an annual rate of 2.7 percent, inflation hit 100 percent a year with a hyperinflationary explosion in 1989, and foreign debt ballooned almost beyond control. This unfortunate record yields some valuable lessons about how to pursue economic growth.